2013
DOI: 10.1371/journal.pone.0079191
|View full text |Cite
|
Sign up to set email alerts
|

Local Perceptions, Cultural Beliefs and Practices That Shape Umbilical Cord Care: A Qualitative Study in Southern Province, Zambia

Abstract: BackgroundGlobal policy regarding optimal umbilical cord care to prevent neonatal illness is an active discussion among researchers and policy makers. In preparation for a large cluster-randomized control trial to measure the impact of 4% chlorhexidine as an umbilical wash versus dry cord care on neonatal mortality in Southern Province, Zambia, we performed a qualitative study to determine local perceptions of cord health and illness and the cultural belief system that shapes umbilical cord care knowledge, att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 36 publications
3
63
0
3
Order By: Relevance
“…The appreciation of the importance of the umbilical cord inside the uterus has also been reported in a similar study in Zambia [2]. However after birth when the umbilical cord was cut and tied and it lingered on the surface of the newborn body, the umbilical cord became a source of fear, dread and uncertainty.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The appreciation of the importance of the umbilical cord inside the uterus has also been reported in a similar study in Zambia [2]. However after birth when the umbilical cord was cut and tied and it lingered on the surface of the newborn body, the umbilical cord became a source of fear, dread and uncertainty.…”
Section: Discussionmentioning
confidence: 55%
“…As a result, interventions that promote hygienic umbilical cord care are listed as prioritized interventions in newborn health [12,16]. Understanding umbilical cord care practices and the rationale behind these practices is vital for the scale up of interventions addressing umbilical cord care [2,6], but very few studies have addressed this issue [2]. Therefore, in this paper, we explore practices associated with umbilical cord care in Central Uganda, and the meanings attached to the cord in this social and cultural context.…”
mentioning
confidence: 99%
“…In India, Reshma and Sujatha (2014) reported that 95% of the mothers apply oil massaging for the baby before bathing, 53% of them provided home remedies for the baby, such as exposing babies to sunlight in case of Jaundice, 55% applied ashes, soot, powder, or dry cow dung on the umbilical cord. Another study in Zambia by Herlihy et al, (2013) found that cord applications included drying agents (e.g., charcoal, baby powder, dust), lubricating agents (e.g. cooking oil, used motor oil) and agents intended for protective and treatment purposes (e.g., breast milk, cow dung, chicken feces) were adotped by the majority of mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Local cord care practices in developing countries included application of charcoal, baby powder, dust, Vaseline, mustard oil, breast milk, cow dung and chicken feces. 10 The recent trends have moved back to dry cord care, without routine application of topical antiseptic agents. These trends have been accepted by American Academy of Pediatrics.…”
Section: Resultsmentioning
confidence: 99%